Consumer Data Protection In Electronic Transaction Practices In E-Commerce - Salim, Alikhan; Susilowati, Tri; Sejati, Hono (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Online transactions provide huge benefits for buyers and sellers. For buyers, the convenience of shopping without having to go to a physical store is the main benefit. They can compare prices and products from various sellers, saving time and transportation costs. For sellers, online transactions open up wider market opportunities, increase product exposure, and increase sales and distribution efficiency. However, the risk of personal data leakage always lurks in online transactions. This issue is serious and can compromise consumers' privacy and information security. Data leaks can occur when personal information such as names, addresses, telephone numbers, emails, credit card details and other personal data falls into unauthorized hands. The research aims to explore the protection of consumers' personal data and examine the responsibility of marketplaces in dealing with data leaks. The author uses a normative juridical approach, which includes primary and secondary legal analysis, as well as descriptive analysis to summarize applicable regulations and legal theory related to practice. The results show that Indonesia has Law Number 27 of 2022 concerning Protection of Consumer Personal Data to protect personal data. Marketplaces that violate these rules may be subject to administrative sanctions in accordance with applicable regulations, while consumers have the right to file a lawsuit for marketplace negligence in accordance with Article 1366 of the Civil Code.